Transmembrane anion transport mediated by halogen bonding and hydrogen bonding triazole anionophores - Bickerton, LEE; Stirling, AJ; Beer, PD; Duarte, F; Langton, MJ (Royal Society of Chemistry, 2020)
Transmembrane ion transport by synthetic anionophores is typically achieved using polar hydrogen bonding anion receptors. Here we show that readily accessible halogen and hydrogen bonding 1,2,3-triazole derivatives can efficiently mediate anion transport across lipid bilayer membranes with unusual anti-Hofmeister selectivity. Importantly, the results demonstrate that the iodo-triazole systems exhibit the highest reported activity to date for halogen bonding anionophores, and enhanced transport efficiency relative to the hydrogen bonding analogues. In contrast, the analogous fluoro-triazole systems, which are unable to form intermolecular interactions with anions, are inactive. The halogen bonding anionophores also exhibit a remarkable intrinsic chloride over hydroxide selectivity, which is usually observed only in more complex anionophore designs, in contrast to the readily accessible acyclic systems reported here. This highlights the potential of iodo-triazoles as synthetically accessible and versatile motifs for developing more efficient anion transport systems. Computational studies provide further insight into the nature of the anion-triazole intermolecular interactions, examining the origins of the observed transport activity and selectivity of the systems, and revealing the role of enhanced charge delocalisation in the halogen bonding anion complexes.